Dose response assessment of conventional Fricke: a relationship between UV-Visible and nuclear magnetic resonance techniques - Ângela Moreira Marques dos Santos; Rita de Cássia de Oliveira Sebastião; Amir Zacarias Mesquita; Thêssa Cristina Alonso; Andrea Mantuano; Telma Cristina Ferreira Fonseca (Brazilian Journal of Radiation Sciences)
Conventional Fricke is an aqueous ferrous sulfate solution that has been widely studied in the field of chemical dosimetry. The feasibility of its use has become attractive for high dose measurements that are of clinical interest in the field of radiotherapy and for industrial purposes, in the irradiation of blood bags and the sterilization of surgical material. The derivation of the absorbed dose of Fricke depends on the radiation-induced oxidation of iron (II) ions (Fe2+) present in the aqueous solution to iron (III) ions (Fe3+), which occurs after exposure to ionising radiation. In this paper, it is proposed to evaluate the dose response of the Fricke dosimeter using two different analytical techniques, ultraviolet-visible spectrophotometry (UV-Vis) and nuclear magnetic resonance spectroscopy (NMR). Twelve groups of samples were analysed in triplicate, irradiated with doses between 0 and 800 Gy, using a cobalt-60 source (60Co). The dose rate of Fricke dosimeters was evaluated against the practical values obtained. The different methods allowed an analytical correlation of the species of oxidised iron (Fe3+) using a linearity curve as a function of the applied radiation dose.